Study on the impact of social capital on the rural residents’ conscious interpersonal waste separation behavior: evidence from Jiangxi province, China - Teng, Yuhua; Li, Ning; Yang, Jing; Liu, Yuan; Liu, Changjin (Frontiers in Environmental Science, 2024)
Guiding rural residents to implement interpersonal waste separation in their daily lives consciously is crucial for controlling solid waste pollution in developing countries. This paper utilizes survey data from Jiangxi Province which is one of the national pilot zones for ecological conservation in China to analyze the impact of the social capital that includes social networks, social trust, and social norms on the rural residents' conscious interpersonal waste separation behavior. The empirical results indicate that social capital has a positive effect on the rural residents' conscious interpersonal waste separation behavior, wherein the effects of social networks and social trust are significant. Among the three dimensions of social capital, social networks and social norms are substitutable, while social trust and social norms have a complementary effect on each other. Moreover, the ecological cognition and subjective norm play a significant mediating role in the relationship between social network, social trust, and social norms and the rural residents' conscious interpersonal waste separation behavior, while the government policies plays a significant moderating effect.